2018
DOI: 10.1016/j.aap.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing noncompliance with bicycle passing distance laws

Abstract: Many jurisdictions around the world have implemented laws to require a minimum distance when motor vehicles pass cyclists, but research into the factors influencing passing distances has produced inconsistent results, indicating the need for future research. This study examined the factors influencing motorists' compliance with a legislated bicycle passing distance rule in Queensland, Australia. Unlike the earlier studies, which used volunteer riders to record passing events, this study used a naturalistic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
3
21
2
2
Order By: Relevance
“…In other regions of Australia (with the exception of our region of Victoria), legalisation or trials of minimum passing distances have been legislated and stipulate that drivers must provide a passing distance of at least 1 metre when the speed limit is 60 km/h or less, and 1.5 metres when the speed limit is more than 60 km/h. In line with our finding that passing distance did not differ between speed zones, and consistent with Debnath et al (2018), 15 we observed a higher proportion of passing events in which the passing distance was less than these suggested boundaries in speed zones of greater than 60 km/h. Given that passing vehicle speed is known to be a major concern for cyclists, 33 speed-based minimum passing distance regulations are justified, and our results demonstrate the need to increase education for drivers to provide greater passing distance at higher vehicle speeds.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In other regions of Australia (with the exception of our region of Victoria), legalisation or trials of minimum passing distances have been legislated and stipulate that drivers must provide a passing distance of at least 1 metre when the speed limit is 60 km/h or less, and 1.5 metres when the speed limit is more than 60 km/h. In line with our finding that passing distance did not differ between speed zones, and consistent with Debnath et al (2018), 15 we observed a higher proportion of passing events in which the passing distance was less than these suggested boundaries in speed zones of greater than 60 km/h. Given that passing vehicle speed is known to be a major concern for cyclists, 33 speed-based minimum passing distance regulations are justified, and our results demonstrate the need to increase education for drivers to provide greater passing distance at higher vehicle speeds.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we observed a mean passing distance of 173cm. This is slightly lower than data from another Australian state, Queensland, in which a mean passing distance of 186cm was reported, 15 and 6.4 ft (195cm) reported in Wisconsin, United States. 13 In contrast to our study, both of these prior studies were conducted in settings with legislated bicycle passing distance rules.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Of the assessed bicycle lane types, exclusive bicycle lanes generally provide the greatest physical separation between bicycles and vehicular traffic, and kerbside bicycle lanes provide the least separation. Greater separation will increase passing distance for motor vehicles and may aid visibility for cyclists and motorists, cue motorists to be aware that cyclists are present, and provide greater protection against human error, thereby leading to fewer crashes (Apasnore et al, 2017;Debnath et al, 2018).…”
Section: Bike Lane Typesmentioning
confidence: 99%